Naples: la storia - Fraia, Luciano de (Italy : Pixel06, 2008)
A documentary about the urban history of Naples. It looks at the town planning of Naples from the ancient Greek settlements up until the current day. The documentary starts with an historical narration for the period from 600 B.B to 1400 A.D. It is full of myths, anecdotes and tales supported throughout by virtual reconstruction and footage shot during archaeological excavations. It moves through the period 1000 to 1657 A.D with interviews with archeologists, historians, vulcanologists and architects, whilst illustrative monuments, buildings, maps and virtual reconstructions of the city of Naples and its surroundings are portrayed in the background. From the year 1900 onwards a number of city planning disasters are outlined. City planner Aldo Loris Rossi, archaeologist Giuseppe De Simone, architectural historian Leonardo Di Mauro, vulcanologist Giuseppe Luongo, art historian Nicola Spinosa and philosopher Aldo Masullo help the viewer through this 2600-year journey.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films